Penerapan model pembelajaran kooperatif tipe two stay two stray (tsts) untuk meningkatkan pemahaman konsep bangun ruang pada siswa kelas v sekolah dasar - Alfonsus David Adi Rismawan; Hadi Mulyono; Suharno Suharno (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2021)
Abstract. The purpose of this research is improving understanding of geometry concept by applicating Two Stay Two Stray cooperative learning model. This researchis Classroom Action Research with two cycles. The subjects of this research were students of the 5th students at11 Ngringo Elementary School of Jaten subdistrict Karanganyar in the academic year of 2017/2018, totalling 32 students. This research uses data collection techniques in the form of interview, observation, i.e. planning, implementation, observation and reflection. The analysis of the data used is the interactive analysis model of Miles-Huberman. The first cycle resulting in a percentage of 40,62% in classical, and the study continued with the second cycle with the percentage of 82,25% in classical terms. Based on the result of the research, it can be conclude that through the application of Two Stay Two Stray cooperative learning model can improve understanding of geometry concept of 5th grade students of 11 Ngringo Elementary School of Jaten subdistrict Karanganyar in the academic year of 2017/2018.